Losing hearts and minds? : public diplomacy and strategic influence in the age of terror - Lord, Carnes (Westport, Conn. : Praeger Security International, 2006)
"Losing Hearts and Minds? situates public diplomacy within the complex environment of U.S. government bureaucracy, and relates it to other instruments of national power, particularly diplomatic activities and military force. The book offers a comprehensive vision of this critical dimension of statecraft, prompting debate by analyzing obstacles to effective public diplomacy."--Jacket.
Introduction -- Strategic influence and soft power -- Public diplomacy and psychological-political warfare -- Strategic influence in the age of terror -- Problems of legitimacy : the cultural context -- Problems of organization : the bureaucratic context -- The State Department : back to the future? -- International broadcasting : who's in charge? -- The Defense Department : into the act? -- The White House : key to the game? -- Strategic influence and the future.
Includes bibliographical references (pages 117-133) and index.
Keywords: War on Terrorism, 2001-2009.; Bureaucracy -- United States; Diplomacy; International relations -- Psychological aspects; Public relations and politics -- United States; Strategic aspects of individual places; Public relations and politics -- United States